Database Sentiment Analysing Prototype About Responsibility and Legal Protection for Violence And abuse of Protected Animals Using NLP - Pasaribu, Rogantino Sampetua (Universitas Trunojoyo Madura, 2024)
The rampant violence against animals often in Indonesia Country. This is a clear example of the lack of public awareness of how to treat animals properly, sanctions that are so light for the perpetrators of torture against the animals themselves, and the lack of decisive action from the authorities. The formulation of the problem in this study is how are the legal responsibility and legal protection of animals. This research method uses a normative juridical approach. Based on the author's research, the following results were found, namely legal liability for animal persecution in the form of criminal sanctions and administrative sanctions. Criminal sanctions can be imposed if the act has violated the provisions contained in Article 302 of the Criminal Code and Article 91B of Law Number 18 of 2009 as amended by Law Number 41 of 2014 concerning animal husbandry and animal health. Legal protection against animal persecution in the form of preventive legal protection and repressive legal protection. The basis is used for the development of sentiment analysis using NLP.